Study Of Parasocial Interaction Between Bangtan Boys (BTS) And Army In Indonesia: The Meaning Of One-Way Closeness Between Fans And Idols - Vidya Alisya; Sharfina Nurhayati; Rino Febrianno Boer (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The relationship that exists between fans and their idols is considered to have a special meaning. The existence of distance and time makes fans only able to see their idol from television or social media which happened in one direction. The one-way relationship builds parasocial interactions between fans and their idols where fans feel they understand, care, and sense how their idols felt. Parasocial interactions were experienced by fans and their idols, including BTS and their fans called ARMY. This study uses a qualitative method. This research on BTS and ARMY aims to find out what forms of parasocial interaction are carried out by ARMYs with BTS and how ARMYs interpret these interactions. The research was conducted on six participants who are ARMYs. Data collection was conducted by interview and literature study. The study was conducted in Jakarta from March to July 2022. The research was conducted by linking the answers of the informants using Hoffner's four parasocial interaction effects, which are sense of companionship, pseudo-friendship, role models in behavior, and personal identity. Researchers found that the parasocial effect is described as a form of admiration of fans for their idols. Also, ARMY considers that the parasocial interactions that occur with BTS have a positive impact and that positive impact were implemented in everyday life